Cleft, Crevice, or the Inner Thigh: ‘Another Place’ for the Establishment of the Invasive Barnacle Austrominius modestus (Darwin, 1854) - Bracewell, Sally A.; Spencer, Matthew; Marrs, Rob H.; Iles, Matthew; Robinson, Leonie A. (PLOS ONE, 2012)
The proliferation of anthropogenic infrastructure in the marine environment has aided the establishment and spread of invasive species. These structures can create novel habitats in areas normally characterised as void of suitable settlement sites. The habitat requirements of the invasive acorn barnacle Austrominius modestus (Darwin, 1854) were assessed using a novel sampling site at Crosby Beach, Liverpool. Austrominius modestus has spread rapidly around the UK since its initial introduction, becoming locally dominant in many estuarine areas including the Antony Gormley art installation, ‘Another Place’, at Crosby Beach. The installation consists of 100 replicate solid cast-iron life-size human figures, located at a range of heights on the shore. We recorded the distribution and abundance of A. modestus present on all of the statues at various positions during the summer of 2006. The positions varied in location, exposure, direction, and rugosity. Although parameters such as rugosity and exposure did influence patterns of recruitment, they were less important than interactions between shore height and direction, and specific location on the beach. The addition of a suitable substrate to a sheltered and estuarine region of Liverpool Bay has facilitated the establishment of A. modestus. Understanding the habitat requirements of invasive species is important if we are to make predictions about their spread and the likelihood of invasion success. Austrominius modestus has already become locally dominant in some regions of the UK and, with projections of favourable warming conditions and the global expansion of artificial structures, the continued spread of this species can be expected. The implications of this on the balance between native and invasive species dominance should be considered.